Perception of local inhabitants outside tourism structures in Governor Generoso, Mindanao, Philippines - Chris Lloyd Ceniza (Borneo Novelty Publishing, 2026)
Purpose – The purpose of this research is to understand the perception and attitude of the local inhabitants residing outside the tourism destinations in the Municipality of Governor Generoso, Davao Oriental, Philippines. This paper examines how local inhabitants perceive the emerging tourism industry in their area. Methodology/Design/Approach – The study utilized the qualitative research design, particularly the phenomenological research method. This method includes several stages, such as data gathering, data analysis, and thematic analysis. The data collection process involves in-depth interviews and focus group discussions. The collected data underwent a thematic analysis to identify themes that emerged in the findings and discussions, providing clear evidence of the participants' perceptions.Finding – The result of the research shows that residents’ perceptions and attitudes are relative to the benefits gained in the tourism industry. Residents benefiting from tourism have affirmative perceptions, while those who find it non-beneficial have negative and neutral perceptions, respectively. Those having an affirmative perception cite that tourism provides job opportunities, government income, beautification of the place, pride and honor for the locals, and leisure and enjoyment for the visiting tourists. Those having an adverse perception and attitude assert that tourism caused inconvenience and infringement on their fishing livelihood. Additionally, job opportunities are limited. It is a threat to their security and safety, and only a privilege for the rich. This affirms that the tourism industry brings about challenges and opportunities to residents living near tourism destinations. More importantly, it greatly affects the marginalized individual.Originality/Value – This study provides scientific and concrete information on how locals perceive the tourism industry developed in their place. This contributes to sustainable tourism development and enhances community well-being and quality of life. Acknowledging the importance of local support to tourism can lead to a sustainable industry, coupled with better-informed decision-making, enhances the cost-benefit analysis, which may be used in crafting better policies that will support and enhance the quality of life and well-being of the locals in the same manner as the tourism industry grows. This would particularly of great value to the local community and people of Governor Generoso, Mindanao, Philippines.